Is informality bad? Evidence from Brazil, Mexico and South Africa - Olivier Bargain; Prudence Kwenda (Institute for the Study of Labor (IZA), 2010)
The informal sector plays an important role in the functioning of labor markets in emerging economies. To characterize better this highly heterogeneous sector, we conduct a distributional analysis of the earnings gap between informal and formal employment in Brazil, Mexico and South Africa, distinguishing between dependent and independent workers. For each country, we use rich panel data to estimate fixed effects quantile regressions to control for (time-invariant) unobserved heterogeneity. The dual nature of the informal sector emerges from our results. In the high-tier segment, self-employed workers receive a significant earnings premium that may compensate the benefits obtained in formal jobs. In the lower end of the earnings distribution, both informal wage earners and independent (own account) workers face significant earnings penalties vis-à-vis the formal sector. Yet the dual structure is not balanced in the same way in all three countries. Most of the self-employment carries a premium in Mexico. In contrast, the upper-tier segment is marginal in South Africa, and informal workers, both dependent and independent, form a largely penalized group. More consistent with the competitive view, earnings differentials are small at all levels in Brazil.
Keywords: J21; J23; J24; J31; O17; 330; Self-employed; salary work; informal sector; earnings differential; quantile regression; fixed effects model; Lohnstruktur; Dualer Arbeitsmarkt; Informeller Sektor; Selbstständige; Arbeitskräfte; Schätzung; Schwellenländer; Brasilien; Mexiko; Südafrika